Approval of unit rate for applying emulsion paint on ceiling and enamel paint in pipes - Kansai Nerolac Paints Ltd.. (Brac University, 2023)
This variation order has been made between Brac University and Kansai Nerolac Paints Ltd.. for approval of unit rate for applying emulsion paint on ceiling and enamel paint in pipes of Brac University new campus project.